2002
DOI: 10.1038/sj.bjc.6600056
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of all-TRANS-retinoic acid metabolism by R116010 induces antitumour activity

Abstract: All-trans-retinoic acid is a potent inhibitor of cell proliferation and inducer of differentiation. However, the clinical use of all-transretinoic acid in the treatment of cancer is significantly hampered by its toxicity and the prompt emergence of resistance, believed to be caused by increased all-trans-retinoic acid metabolism. Inhibitors of all-trans-retinoic acid metabolism may therefore prove valuable in the treatment of cancer. In this study, we characterize R116010 as a new anticancer drug that is a pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 21 publications
(22 reference statements)
0
79
1
Order By: Relevance
“…superior to the effects observed with R116010 in human breast T47D cancer cells (Van Heusden et al, 2002). In the latter study, R116010, at a concentration of 1 mM, enhanced the antiproliferative activity of ATRA only by threefold.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…superior to the effects observed with R116010 in human breast T47D cancer cells (Van Heusden et al, 2002). In the latter study, R116010, at a concentration of 1 mM, enhanced the antiproliferative activity of ATRA only by threefold.…”
Section: Discussionmentioning
confidence: 54%
“…Although a first generation RAMBA, liarozole has been shown to exhibit potent antitumour efficacy against human androgen-independent PCA tumours, such as PC-3ML-B (Stearns et al, 1993), and DU-145 (Smets et al, 1994) and several rat PCA tumours (De Coster et al, 1992;Dijkman et al, 1994); this study appears to be the first report on the antitumour efficacy of RAMBAs against human androgen-dependent LNCaP PCA tumours. Recently, it was demonstrated that a second generation RAMBA, R116010, was able to significantly inhibit the growth of murine TA3-Ha mammary tumours in A/J mice (Van Heusden et al, 2002). Given that our RAMBAs exhibited potent in vitro antiproliferative activities, their in vivo antitumour efficacies are rather disappointing.…”
Section: Discussionmentioning
confidence: 99%
“…A dose of 66.0 mmol kg À1 day À1 caused a reduction of 92.6% in the mean final tumour weight compared with that of tumour-bearing mice receiving vehicle alone, with no apparent toxicity as there was no change in body weight of the mice. It was recently reported that the growth of murine oestrogen-independent TA3-Ha mammary tumours were significantly inhibited by a non-retinoidal RAMBA, R116010 (Van Huesden et al, 2002). The study demonstrated the antitumour efficacy of R116010 in an oestrogen-independent model of un-established tumours and it is not clear if the agent is effective against oestrogen-dependent breast tumours.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, in vitro inhibition of CYP26 leads to an increase in differentiation, decrease in proliferation, cell adhesion and metastatic potential. This has led to the suggestion of a possible chemoprevention role of using specific CYP26 inhibitors (Wouters et al, 1992;Van Heusden et al, 2002). In addition, RA metabolism-blocking agents lead to a reduction of tumour size in mouse xenograft models (Patel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%